Theoretical-Conceptual Bases Of Intellectual Capital Management In The Activities Of Managers Of Vocational Educational Institutions (Texas Journal of Multidisciplinary Studies, 2025)
The article studied the theoretical and conceptual foundations of intellectual capital (IC) management in the context of vocational education institutions (VEIs). The essence and interrelation of human, structural, and relational capital as intangible assets of an educational organization were critically analyzed. Based on the analysis, a conceptual structure for managing intellectual capital, specifically adapted for the activities of a VEI head, was developed and substantiated, which incorporates specific management directions aimed at developing each type of capital. The significance of this structure in achieving the strategic goals of Uzbekistan's education system, particularly in enhancing the competitiveness of institutions and the employability of graduates in the labor market, was determined.